A tailored aggregation strategy for inventory pooling in healthcare: evidence from an emerging market - El Mokrini, Asmae; Aouam, Tarik; Kafa, Nadine (Operations management research, 2023)
Pharmaceutical consumption in hospitals and healthcare centers is characterized by demand uncertainty, particularly during unusual events, e.g., pandemics and other crises. Unlike other industries, healthcare management has been slow in implementing effective business logistics concepts, e.g., inventory pooling, i.e., aggregation, and extant literature on this topic is scant. Inspired by a public pharmaceutical supply chain, this study aims to investigate the feasibility and relevance of hospitals and other health care facilities collaborating through inventory pooling. While important savings could be achieved through aggregation, this strategy comes at a cost. In this study, we present a model that captures the costs of inventory pooling in an emerging market setting to find the optimal tailored aggregation, set of demand points, and products to aggregate so that inventory pooling costs and savings are balanced. The problem has been formulated as a mixed-integer conic quadratic program to minimize the total cost of pooling and hold safety stocks in the supply network, subject to budget constraints. We applied the proposed model to a real case study of pharmaceutical distribution in Morocco and analyzed inventory pooling schemes under different budget allocations to investigate how regional and product disparities affect costs and inventory pooling decisions. The findings reveal that when changing the pooling budget, the best customized aggregation varies substantially and is influenced by product type, regional population density, income per capita, and urbanization rate.